Therapeutic ultrasound in navicular stress injuries in elite track and field athletes - Malliaropoulos, N.; Alaseirlis, D.; Konstantinidis, G.; Papalada, A.; Tsifountoudis, I.; Petras, K.; Maffulli, N. (Clinical Journal of Sport Medicine, 2017)
Objective: To ascertain whether therapeutic ultrasound (TUS) can be used to assess the progression of conservative management in navicular stress injuries. Design: This is a prospective, clinical case series. Level of evidence IV. Setting: All participants were examined and followed up in a private Sports Injury Clinic. Participants: Ten elite track and field athletes with severe dorsal midfoot pain over the navicular bone participated in this study. Interventions: All patients underwent both TUS and magnetic resonance imaging (MRI) evaluation. The painful threshold of TUS on initial evaluation was a mean of 0.707 ± 149 W/cm², and MRI detected a navicular stress injury in all patients. The athletes received conservative treatment and underwent sequential TUS evaluations at 4, 8, 12 and 16 weeks. Main Outcome Measures: Therapeutic ultrasound pain threshold values were recorded, and the patients were additionally asked to grade local tenderness on a Visual Analogue Scale. Time to return to play was also recorded. Results: The level of pain produced by the application of TUS on a navicular stress fracture seemed to correlate well with Visual Analogue Scale scores and the grade of fracture demonstrated on MRI. The initial low TUS painful mean value increased to a normal mean value of 1.97 ± 0.067 W/cm² by 16 weeks. When clinical and TUS findings had returned to normal, the patients were allowed to return to sports activities, with no recurrences experienced during the study period. Conclusions: The production of pain associated with the application of TUS on a navicular stress fracture is a safe and reproducible method of monitoring the resolution of these fractures. We have used it successfully in making return-to-play decisions for elite level track and field athletes. ABSTRACT FROM AUTHOR